2022
DOI: 10.5398/tasj.2022.45.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Dietary Exposure Assessment of Fluoroquinolones Residues in Chicken Meat from the Districts of Malang and Blitar, Indonesia

Abstract: The purpose of this study was to determine the presence of fluoroquinolones (enrofloxacin and ciprofloxacin) residues in fresh chicken meat and evaluate its consumption risk to the adult population in Indonesia. A total of 55 fresh chicken-meat samples were collected from Districts of Malang and Blitar, East Java Province, Indonesia, in April 2017. Detections of enrofloxacin and ciprofloxacin were carried out using high-performance liquid chromatography equipped with a PDA detector. It was found that ciproflox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Ciprofloxacin residues in chicken liver were detected at 44%, thighs at 34%, and breast at 30% ( Sattar et al ., 2014 ). Likely, Widiastuti et al . (2022 ) reported that 67.3% of chicken meat had ciprofloxacin residues, with a mean concentration of 91.22 ± 70.49 ng/g.…”
Section: Discussionmentioning
confidence: 85%
“…Ciprofloxacin residues in chicken liver were detected at 44%, thighs at 34%, and breast at 30% ( Sattar et al ., 2014 ). Likely, Widiastuti et al . (2022 ) reported that 67.3% of chicken meat had ciprofloxacin residues, with a mean concentration of 91.22 ± 70.49 ng/g.…”
Section: Discussionmentioning
confidence: 85%
“…In a previous study, a total of 127 chicken meat samples were studied to detect quinolones from Ankara, Turkey, where 45.7% of samples were positive for quinolones and the mean level of quinolones was found to be 30.81 μg/kg [ 42 ]. In other studies, data on the occurrence of enrofloxacin or/and ciprofloxacin in chicken were found for Portugal [ 4 , 27 ], Indonesia [ 28 ], Korea [ 29 ], Lebanon [ 30 ], Sri Lanka [ 31 ], South Africa [ 32 ], and Vietnam [ 33 ], with a detected frequency in the range of 4.2–51.9% and 5.17–67.3%, respectively, which was higher than that observed in our study (3.36% and 1.14%). This result indicated that these antibiotics are widely used in the world.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, seven (12.1%) of the chicken meat samples were positive for enrofloxacin, but only three (5.2%) of the chicken meat samples were positive for ciprofloxacin in Korea [ 29 ]. On the contrary, the detection frequencies of enrofloxacin residues were found to be lower than that of ciprofloxacin in chicken samples in Indonesia (41.8% and 67.3%), Lebanon (12.5% and 32.5%), and Portugal (51.0% and 60.4%) [ 4 , 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIP tends to accumulate in aquatic environments, due to its low biodegradability, eventually leading to high concentrations [ 11 , 12 ]. CIP can also disperse into the foodchain via trophic transfer [ 13 , 14 , 15 , 16 , 17 ]. In addition, a sub-inhibitory dose of CIP may lead to the development of resistance to antimicrobial drugs, therefore it poses threats to both environmental and human health [ 18 ].…”
Section: Introductionmentioning
confidence: 99%